Floristic diversity in the Kashmir Himalaya: progress, problems and prospects - Dar, G.H.; Khuroo, A.A. (Universiti Kebangsaan Malaysia, 2013)
The Kashmir Himalaya, being nestled within north-western folds of the Himalaya, harbours a rich floristic diversity of immense scientific interest and enormous economic potential. Though scientific studies on the floristic diversity in the Kashmir Himalaya have been started about two centuries ago, yet they fall short of the requirements needed urgently in the post-Rio Summit. In fact, at the spatial scale, many far flung areas and difficult terrains in the hinterland are still either least- or totally-unexplored; and at the taxon scale, floristic studies especially with regard to the lower plants are insufficient, thus posing serious problems in assessing the floristic diversity in the region. With such a perspective in hindsight, the present paper dilates upon the progress achieved so far, highlights the problems being faced and envisages the future prospects with regard to floristic diversity in this region. First, a broad overview of the current status of floristic diversity in this Himalayan region is presented, followed by a critical analysis of the knowledge base presently available on various taxonomic groups of plants. The yawing gaps in our knowledge of floristic diversity in this region are identified and an action plan to bridge these gaps is also outlined. Hopefully, addressing these challenges in the immediate future could facilitate the documentation, conservation and sustainable use of plant resources in this region, so as to steer this ‘Himalayan Paradise’ towards the path of sustainable development.